Perlindungan Hukum Tari Sanghyang Memedi Sebagai Ekspresi Budaya Tradisional Di Desa Adat Pangkung Karung Gede Kabupaten Tabanan - I Gusti Made Agung Satria Putra; I Wayan Wesna Astara; Diah Gayatri Sudibya (Jurnal Analogi Hukum, 2025)
Indonesia's arts and culture are diverse and valued as national treasures. Copyright law protects traditional cultural expressions owned by communal communities. The Sanghyang Memedi dance performed in Pangkung Karung Gede Traditional Village is one example of such expression. However, this dance is gradually being forgotten due to its sacred nature and limited performance opportunities based on Balinese customs and culture. The formulation of the problem raised is 1) How is the legal protection of Sanghyang Memedi dance in Pangkung Karung Gede Traditional Village, Tabanan Regency as a Traditional Cultural Expression? and 2) Factors that become obstacles in the legal protection of Sanghyang Memedi dance in Pangkung Karung Gede Traditional Village, Tabanan Regency as a traditional cultural expression? This research uses empirical legal research, namely the gap between a norm and the situation in society. The results of this study indicate that the Sanghyang Memedi Dance in the Pangkung Karung Gede Traditional Village of Tabanan Regency does not receive copyright protection because people do not understand its importance. To overcome this, the government needs to educate and collect information from artists and communities in the village.